2018
DOI: 10.2147/cmar.s160924
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide potentiates the antitumor effect of topotecan in acute myeloid leukemia cells through an intrinsic apoptotic pathway

Abstract: BackgroundTopotecan (TP) is an anticancer drug acting as topoisomerase I inhibitor that is used in the treatment of many types of cancers including leukemia, but it has significant side effects. Andrographolide, a compound extracted from Andrographis paniculata, was recently proven to inhibit the growth of cancer cells and can induce apoptosis. The aim of this study is to investigate the possible synergism between TP and andrographolide in acute myeloid cells in vitro.Materials and methodsU937 acute myeloid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…61 Many signaling pathways are involved, including p53-mediated activation of pro-apoptotic factors as a result of DNA double-stranded breaks, MAP-kinase activation, and the capacity for DNA repair. [62][63][64] It was previously demonstrated that Ru(II) anticancer drugs can trigger DNA damage which in turn activates apoptosis via the intrinsic pathway. 65 Zhang and coworkers reported the intercalative potential of Ru(II) polypyridyl complexes which were shown to induce apoptosis in A549 cells, as concluded from ow cytometric studies.…”
Section: Resultsmentioning
confidence: 99%
“…61 Many signaling pathways are involved, including p53-mediated activation of pro-apoptotic factors as a result of DNA double-stranded breaks, MAP-kinase activation, and the capacity for DNA repair. [62][63][64] It was previously demonstrated that Ru(II) anticancer drugs can trigger DNA damage which in turn activates apoptosis via the intrinsic pathway. 65 Zhang and coworkers reported the intercalative potential of Ru(II) polypyridyl complexes which were shown to induce apoptosis in A549 cells, as concluded from ow cytometric studies.…”
Section: Resultsmentioning
confidence: 99%
“…MDA-MB-231 cells were seeded into 6 well plates at a density of 10 5 cells/mL. Cells, except the controls, were treated with 10, 20, and 30 µM of beta-tocotrienol after a 24 h incubation period (37 • C in a humidified atmosphere containing 5% CO2), After the desired period of treatment (24 h), the cellular proteins were extracted using Q-proteome Mammalian Protein kit (QIAGEN) as previously described [52]. Proteins were quantified using Lowry assay.…”
Section: Protein Extraction and Western Blotsmentioning
confidence: 99%
“…Currently, combinations of chemotherapeutic drugs constitute the backbone of AML treatment, with a wide spectrum of different side effects, starting with anemia, hair loss, and diarrhea, in addition to nervous and fertility problems later [3]. Over the years, the serious adverse effects of chemotherapy treatment have stimulated researchers to divert their focus towards natural compounds that may be effective in treating various malignancies, including leukemia, with lower toxicity [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%